Clinical features and management of postoperative lumbar intervertebral space infections following spinal endoscopy: a retrospective analysis - Su, Kunpeng; Liu, Mingzhi; Wang, Mengxuan; Yao, Qingyu; Wang, Zirui; Lian, Zheng; Zhou, Chuanli (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPostoperative lumbar intervertebral space infections following spinal endoscopy are infrequent but severe complications that can markedly affect patient recovery and treatment outcomes. Early diagnosis remains challenging due to the nonspecific nature of clinical symptoms. This study aims to identify the clinical characteristics, risk factors, and effective diagnostic and treatment strategies for postoperative intervertebral space infections.MethodsA retrospective analysis was conducted on 14 cases of postoperative intervertebral space infections following spinal endoscopy. The data set included patient demographics, clinical symptoms, imaging findings, blood culture results, and treatment approaches. The analysis assessed early diagnosis and treatment outcomes concerning the infection’s progression and the use of MRI, inflammatory markers, and empirical antibiotics.ResultsThe most common clinical symptoms included localized back pain, neurological deficits, and fever, though these lacked specificity. MRI proved valuable in diagnosing early infections. The majority of cases exhibited elevated levels of inflammatory markers, such as CRP and ESR. The treatment plan included early surgical intervention with debridement and internal fixation, along with extended antibiotic therapy.ConclusionThe early identification and intervention of postoperative intervertebral space infections following spinal endoscopy are of critical importance. The implementation of a strict aseptic technique, the execution of careful preoperative planning, and the timely use of MRI for diagnosis are essential to the prevention and effective treatment of these infections. This study underscores the necessity of a comprehensive approach to minimize the risk of postoperative intervertebral space infections and to enhance patient outcomes.